Identidade docente de profissionais liberais que atuam na educação superior - Lima, Maria Valeria Lisboa Abreu (2006)
This paper aims at idenlifying, dcscribing and analysiog the professors' representation, acting in acadernic formation, about the teaching and learning process and the Higher Education goals, trying to comprehend ihe elemenis of the consriruiion process of the docent identity in rofessors. Among the authors who are part of the theoretical suppofl to construct thiinsI search we can outstand: Alves, Costa, Freire, Sacristán and Gómez, Chauí, Pimenta and Anastasiou, Masetto, Pinto, Heller, PimenteI, Perrenoud, Behrens, Alves Zabalza, Ciarnpa, Nóvoa, Bnezinski, Hall, Arroyo, Moscovici, Guareschi, Penin, Queluz, Rangel, among others. The starting point is the refleclion about Higher Education and the current teaching process inquiring about the pedagogical practice and the professional formation of the Higher Educariori professors, their identities and the professional consiruction rcgarding teaching, based on the Social Rcpresentation Theory by Moscovici as means of getting in to the teaching identity. Data from three professors, who act in different fields, are andysed in this paper by using the recurrent interview technique as methodological source in an interpretative perspective of the representation of the subjects in order to the proposed aims. The representations about the teaching and learning process and the Higher Education concerns were analysed from a prirnary work of verbalization, Lhrough which data related to teaching development, work and action wcre organized, the daily pedagogical practice, ihe rneaning of teaching in their personal and professional lives and the relrition between education and I society. From ihe study of representations we could infer that the three professors "have learned" how to be professors in red situations of teaching, through shared situations with their peers, one in relation to each othcr, rnainly in thc daily contact with Lheir students,hrough thc context of their lives, personal histories and social powers. During their professional development these professors construct, deconstruct recompound teaching features in the search of the experiment of being professors, ihey identify themselves with teaching trying to feel professors and expressing a ieaching identity which rnakes them engaged with the students and the activities they are involved in. It is not an ideal docent iden tity conformed by the didactic-pedagogical prerogatives. It is not even the presence of a homogenous or unique iden ti ty for ihe three professors.Furthermore, the obtained data have shown thai the three searched subjects have defined their professional self-i mages by contouring a possible docent identity among the severa1 social roles they reguIarly play, peculiar to each one of them, and that not only conform their professional self-images and frarne relevant aspects of the pedagogical practice but also gratifies, ideniifies them md puts them coser to the docent activity they perform.